Urban Social Movements and Regional Problem (Arequipa, 1967-1973) - Durand A. N., Francisco (1979)
The regional scene is today the object of healthy attention by historians and social scientists, who have begun to analyze the real fabric of Peru as a nation in its formative process. Within this regional scene, one of the most interesting social dynamics is the one that the south offers and, within it, Arequipa stands out for its relevant and distinctive role throughout history: it is enough to remember the significance of Arequipa's liberalism led by Lino Urquieta and Francisco Montajo at the beginning of the century; and the chain of frontist social movements that shook the Odriísta dictatorship in the 1950s. In the following decades, the movements had more of a trade union and popular character in terms of the leadership and social base of the mass phenomena.